Papua New Guinea School Autonomy and Accountability : SABER Country Report 2013 - World Bank Group (World Bank, Washington, DC, 2016)
In 2011, the World Bank Group commenced a multi- year program designed to support countries in systematically examining and strengthening the performance of their education systems. Part of the Bank’s new Education Sector Strategy, this evidence based initiative, called SABER (Systems Approach for Better Education Results), is building a toolkit of diagnostics for examining education systems and their component policy domains against global standards, best practices, and in comparison with the policies and practices of countries around the world. By leveraging this global knowledge, the SABER tools fill a gap in the availability of data and evidence on what matters most to improve the quality of education and achievement of better results. SABER School Autonomy and Accountability is the first of three SABER domains to be implemented as part of phase two of the Pacific Benchmarking for Education Results (PaBER) initiative. Funded by AusAID, the PaBER initiative aims to link policy with implementation to identify areas to strengthen policy, improve knowledge dissemination, and improve the quality of education and student performance across the pacific. Specifically, the PaBER project focuses at the primary level of an education system. The project concept and determination of three pilot countries Samoa, the Solomon Islands, and Papua New Guinea was agreed upon at the Pacific Forum Education Ministers Meeting and is being coordinated through the Secretariat of the Pacific Board for Educational Assessment (SPBEA). The SABER School Autonomy and Accountability tool assists in analyzing how well developed the set of policies are in a given country to foster managerial autonomy, assess results, and use information from assessments to promote accountability. The five main policy goals that can help benchmark an education system’s policies that enable school autonomy and accountability were as follows: 1) school autonomy in the planning and management of the school budget; 2) school autonomy in personnel management; 3) role of the School Council in school governance; 4) school and student assessments; and 5) accountability.